2022
DOI: 10.3390/ma15113977
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Fractures of Heterogeneous Orthotropic Fiber-Reinforced Concrete with Pre-Existing Flaws Using an Improved Peridynamic Model

Abstract: The propagation and coalescence of cracks in fiber-reinforced concretes (FRCs) is the direct cause of instability in many engineering structures. To predict the crack propagation path and failure mode of FRCs, an orthotropic-bond-based peridynamic (PD) model was established in this study. A kernel function reflecting long-range force was introduced, and the fiber bond was used to describe the macroanisotropy of the FRC. The crack propagation process of the FRC plate with flaws was simulated under uniaxial tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…9: 221013 the study of Zhang et al [54]. Considering that the main purpose of this paper is to use the improved BB-PD model to study the crack propagation speed, path and coalescence mode of rock specimens containing pre-existing flaws with different number, length, inclination and rock bridge inclination, the differences of simulation results under different shape parameters are not compared, and the relevant research conclusions can be referred to references [54,63].…”
Section: Compression Simulation Of Rock Specimen With Three Pre-exist...mentioning
confidence: 99%
See 1 more Smart Citation
“…9: 221013 the study of Zhang et al [54]. Considering that the main purpose of this paper is to use the improved BB-PD model to study the crack propagation speed, path and coalescence mode of rock specimens containing pre-existing flaws with different number, length, inclination and rock bridge inclination, the differences of simulation results under different shape parameters are not compared, and the relevant research conclusions can be referred to references [54,63].…”
Section: Compression Simulation Of Rock Specimen With Three Pre-exist...mentioning
confidence: 99%
“…Notably, there are some differences between the simulated fracture mode and the test results, which may be due to factors such as rock heterogeneity, anisotropy and microcracks in the rock used in the test. In another study [ 63 ], we found that the smaller the shape parameter m is, the stronger the heterogeneity is, the more serious the damage of the specimen is, and the crack is easier to expand. This conclusion is consistent with the study of Zhang et al .…”
Section: Model Validationmentioning
confidence: 99%
“…In recent years, PD-based computational methods have been widely used to investigate the toughening mechanisms of innovative materials [ 30 , 31 , 32 , 33 ]. Some relevant applications of PD-based tools to study the fracture mechanism of fiber-reinforced concretes can be found in [ 9 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. However, in the existing literature, the fracture analysis on the fiber-reinforced concrete structures is only considered in plane stress or plane strain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PD can predict damage development without additional assumptions as in the CCM, for example, crack extension criteria and node enrichment functions. PD provides a powerful tool to analyze material and structural failure processes [4,5], and has already been successfully applied to various problems, such as deformation and fracture simulation for brittle materials [6][7][8][9][10][11], asphalt [12], ferrite and pearlite wheel materials [13] and composite beams [14], etc.…”
Section: Introductionmentioning
confidence: 99%